2014
DOI: 10.1177/1758573214536536
|View full text |Cite
|
Sign up to set email alerts
|

Biologics in rotator cuff surgery

Abstract: Pathologies of the rotator cuff are by far the most common cause of shoulder dysfunction and pain. Even though reconstruction of the rotator cuff results in improved clinical outcome scores, including decreased pain, several studies report high failure rates. Orthopaedic research has therefore focused on biologically augmenting the rotator cuff reconstruction and improving tendon-bone healing of the rotator cuff. This biological augmentation has included the application of different platelet concentrates conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…¶ This increase in included studies allowed for sufficient numbers to be subgrouped into PRP and PRF, as no other meta-analysis had done this. This increase in numbers also allowed for sufficient power to detect a difference in larger tears, as previous studies had found a significant difference in tears <3 cm 6,40,49 but for tears >3 cm, because they were limited by the lack of numbers to detect a difference. Previous studies have not identified a difference in functional outcomes when using PRP.…”
Section: Discussionmentioning
confidence: 99%
“…¶ This increase in included studies allowed for sufficient numbers to be subgrouped into PRP and PRF, as no other meta-analysis had done this. This increase in numbers also allowed for sufficient power to detect a difference in larger tears, as previous studies had found a significant difference in tears <3 cm 6,40,49 but for tears >3 cm, because they were limited by the lack of numbers to detect a difference. Previous studies have not identified a difference in functional outcomes when using PRP.…”
Section: Discussionmentioning
confidence: 99%
“…There is continued interest in biologic therapies to improve tendon to bone healing in rotator cuff repairs [2,6,29,31]. The cell-based therapy using progenitor cells is a promising strategy for regeneration and healing of the tendon tissues [1, 6, 10, 11, 19, 23, 24, 26-28, 30, 36, 37].…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 43 Because of the inconsistent healing despite significant improvements in mechanical fixation, biological strategies to augment the surgical repair, including bioresorbable scaffolds, have been introduced in an effort to improve the rate of tendon healing. 39 …”
mentioning
confidence: 99%